(untitled) (REVISTA NODO, 2020)
It seeks to understand the development of women’s lives, their condition in public and private environments, how these events intervene in the urban space, and how the advances conquered by women along with this path influence today’s cities. To conduct the study about women’s history, we considered the first civilizations, formed from the development of cities to the contemporary city, promoting a reflection on how the universalization of the city’s population affects women’s and socially excluded groups’ lives, and the challenges to be overcome to build more inclusive cities.